Kinematics Calibration Method for Six-axis Industrial Robot based on Laser Scanning Measuring Arm - Zhang Xuye; Li Qunming; Han Zhiqiang; Guo Weiwei (Jixie chuandong)
A six-axis industrial robot kinematics calibration method based on laser scanning measurement arm measurement system is proposed. Firstly，the motion deviation of the robot itself is analyzed and the problem of non-coincidence between the robot coordinate system constructed by the measurement system and the real base calibration system is comprehensively considered. The absolute positioning error equation related to the parameters of each end of the robot is established, based on the error equation，using the portable laser scanning measurement arm measurement system, the flange center point of the robot in different spatial position posture is measured, and the error equation is solved by least square method. By using the calculated parameter error, the nominal parameters in the robot model are corrected, the accuracy of the robot movement can be improved. By applying the method to the Staubli TX90 industrial robot，the experimental results show that the absolute positioning accuracy of the robot is reduced from the mean/standard deviation of 0.742 5 mm/0.191 0 mm before calibration to 0.242 8 mm/0.098 1 mm after calibration，which is increased by nearly 50%，indicating the validity and accuracy of the calibration method.